Role of dual biomarkers and uterine artery doppler study in predicting PIH and IUGR in antenatal patients registered in a tertiary care centre - Bapat, Alka C.; Kashikar, Rupesh; Goyal, Shashi R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The incidence of IUGR is between 3 to 7%, whereas that of Hypertensive disorders of pregnancy is about 10% of pregnant women around the world. These conditions are associated with a high rate of perinatal morbidity and mortality, posing a need for the detection of the potential causes of maternal and foetal morbidity and mortality and for the prediction of these conditions early during pregnancy. Methods: Patients with first antenatal visit before 10 weeks gestation underwent routine NT scan between 11–13 weeks with bilateral UAD-RI of the maternal uterine arteries. The placental volume was assessed. Serum dual biomarker test (β hCG and PAPP-A) was performed after this scan and analysed as multiples of median (MoM). Blood pressure was recorded at every ANC visit till 2 weeks after delivery. Neonatal head and chest circumference, birth length and weight were recorded. Results: The mean values of PAPP-A levels of Non-PIH and PIH groups were 1.32±0.91 MoM and 0.68±0.39 MoM respectively, showing statistically significant difference. The serum PAPP-A levels showed statistically significant difference between Non-IUGR and IUGR groups (1.24±0.87 MoM and 0.46±0.20 MoM respectively). Conclusions: In our study, PAPP-A level is observed as a good indicator for possible prediction of PIH and IUGR whereas levels of β hCG and UAD-RI were not good predictors. The role of Placental volume in prediction of IUGR needs to be explored further with larger sample size. Future studies are needed with a larger group with inclusion of measurement of PI values.